Review of CO2 Reduction Technologies using Mineral Carbonation of Iron and Steel Making Slag in Malaysia - Siti Norhana, Selamat; Nik Hisyamudin, Muhd Nor; Muhammad Hanif, Abdul Rashid; Mohd Fauzi, Ahmad; Fariza, Mohamad; Al Emran, Ismail; Mohd Fahrul, Hassan; Faiz, Mohd Turan; Zamzuri, Hamedon; Elmi, Abu Bakar; Seiji, Yokoyama (IOP Publishing, 2017)
Climate change, greenhouse gas effect, and global warming is envisioning to turn more awful and more terrible by year. Since the leading cause of global warming is uncontrolled CO2 in atmosphere. The amount of unused steel slag is expected to increment later on, steel industries is one of the mechanical industries that contribute the CO2 emission. That because this businesses deliver carbon in light of powers reductant and substantial volume of steel. The changes of atmosphere these day is truly developing concern and that make steel creator are confronted with test of discovering methods for bringing down CO2 emission. Malaysia is working decidedly in the diminishment of CO2 gas. There are a few techniques in decreasing the amount of CO2 in the air as underlined by the Intergovernmental Panel of Climate Change (IPCC), an organization under the United Country however CCS is an extremely encouraging innovation to moderate CO2 emission in air. Mineral carbonation is another technique to store carbon dioxide permanently, long term stability and vast capacity.